Genetic diversity of pathogenicity islands (PAIS) of uropathogenic escherichia coli (UPEC) strains from Perak, Malaysia - Chin, Jia Jin (2023)
Urinary tract infection (UTI) is a severe health issue worldwide that is primarily caused by uropathogenic Escherichia coli (UPEC). Hundreds of UPEC lineages with various phylogenetic backgrounds and virulence-associated traits have been reported worldwide, but the genetic profiles of UPEC strains remain largely unexplored in Malaysia. Therefore, this study aimed to examine the key molecular characteristics of the UPEC strains in Perak, Malaysia. A total of 105 UPEC strains were collected from a government-funded hospital in Perak, and their resistance profiles against 15 antimicrobials were determined through the disc diffusion method. Template DNAs were extracted using the fast-boil method. The distribution of the phylogroups, 32 virulence genes (VGs), eight pathogenicity island (PAI) markers and the genetic diversity of the UPEC isolates were determined through multiplex polymerase chain reactions. In this study, most UPEC strains were multidrug-resistant (MDR) (53/105; 50.5%) and showed the greatest resistance towards ampicillin (72/105; 68.6%), followed by levofloxacin (36/105; 34.3%). Common virulence-associated traits included fimH (102/105; 97.1%), PAI IV536 (91/105; 86.7%), fyuA (90/105; 85.7%) and chuA (88/105; 83.8%). Phylogroup B2 was the predominant phylogroup iii (67/105; 63.8%) that exhibited consensus virulence-associated traits of fimH, yfcV, kpsMT II, fyuA, chuA, malX, PAI IV536 and PAI ICFT073 (63/67; 94.0%). Surprisingly, phylogroup B2 demonstrated significantly less MDR (p= 0.018) but exhibited the most virulence-associated traits. Among the eight clonal groups (CGs) (18/105; 17.1%), CG1 was dominant and displayed the highest number of virulence-associated traits. UPEC strains isolated from female patients (80/105; 76.2%) displayed a lower prevalence of MDR (p= 0.527) and virulence-associated traits, whereas those collected among the predominant 60- 79 age group (42/105; 40.0%) were significantly more MDR (p= 0.002) and carried fewer virulence-associated traits than other age groups. In conclusion, this study elucidated multiple molecular characteristics of the UPEC strains in relation to the host age and gender in Perak